Iron load in the normal aging brain measured with QSM and R2* at 7T: findings of the SENIOR cohort - Guevara, Miguel; Roche, Stéphane; Brochard, Vincent; Cam, Davy; Badagbon, Jacques; Leprince, Yann; Bottlaender, Michel; Cointepas, Yann; Mangin, Jean-François; de Rochefort, Ludovic; Vignaud, Alexandre (Frontiers in Neuroimaging, 2024)
Background Iron accumulates in the brain during aging and is the focus of intensive research as an abnormal load, particularly in Deep Gray Matter (DGM), is related to neurodegeneration. Magnetic Resonance Imaging (MRI) metrics such as Quantitative Susceptibility Mapping (QSM) and apparent transverse relaxation rate R2* can be used to follow up iron in vivo. While the influence of age and sex on iron levels has already been reported, a careful consideration of neuronal risk factors, as well as for an enhanced sensitivity, is needed to define the normal evolution. Methods QSM and R2* at ultra-high field MRI are used to study iron in DGM using a carefully-characterized cohort of the healthy aging brain (SENIOR). Seventy-seven cognitively healthy elders (from 54 to 78 y/o) with clinical, biology, genetics, and cardiovascular risk factors careful evaluation. Differences linked with age, sex, cardiovascular risk factors and weight are studied. Results Age and sex have an influence on the brain iron deposition measured by QSM and R2* in a context of normal aging, without appearance of a pathological neurodegenerative process. Iron deposition shows higher values in the caudate and the putamen in older participants. Female participants present a higher level of iron in the amygdala, and males in the thalamus. Female participants also present differences in the accumbens, caudate and hippocampus when evaluating the joint age and sex effect. Participants with higher cardiovascular risk factors showed higher values of the iron, even without any impairment in their cognitive capability. An overweight is related with a higher iron load in the putamen for QSM and R2* in female participants. We controlled that these modifications of iron deposition are not related to a specific profile in the genotype of ApoE loci. Conclusions Establishing baseline values of QSM and R2* as iron probes in the context of aging is essential to determine differences in the process of neurodegeneration. Age and sex of participants are important factors that affect brain iron normal values. On the other hand, the presence of cardiovascular risk factors, which can be associated with age related diseases, can also potentially be linked with the iron deposition in the brain.